Apically extruded debris associated with ProTaper Next, ProTaper Gold and TruNatomy systems: An in vitro study - Neslihan Yılmaz Çırakoglu; Yağız Özbay (Tabriz University of Medical Sciences, 2021)
Background. This research aimed to investigate and compare the amount of apically extruded debris after root canal preparation using ProTaper Next, ProTaper Gold, and TruNatomy systems. Methods. Forty-five extracted mandibular premolar teeth with single canals with similar lengths were used. The root canals were prepared using ProTaper Next (Dentsply Maillefer, Ballaigues, Switzerland), ProTaper Gold (Dentsply Maillefer, Ballaigues, Switzerland), or TruNatomy (Dentsply Maillefer, Ballaigues, Switzerland) files. Apically extruded debris during preparation was gathered into preweighed Eppendorf tubes. Then the Eppendorf tubes were incubated at 70°C for five days. The Eppendorf tubes were weighed again to determine their final weight plus the extruded debris. Results. The TRN system resulted in significantly less debris extrusion than the PTN system (P<0.05). There was no significant difference between the PTN and PTG groups and between the PTG and TRN groups (P>0.05). Conclusion. All the instrumentation systems caused apical extrusion of debris. However, the TRN system resulted in significantly less debris extrusion than the other systems.